Evaluating and Comparing the Natural Cell Structure and Dimensions of Honey Bee Comb Cells of Chinese Bee, Apis cerana cerana (Hymenoptera: Apidae) and Italian Bee, Apis mellifera ligustica (Hymenoptera: Apidae). Issue 4 (2nd July 2021) - Yang, Shunhua; Deng, Shangkao; Kuang, Haiou; Zhou, Danyin; Gong, Xueyang; Dong, Kun
Abstract: The hexagonal structure of the honey bee comb cell has been the source of many studies attempting to understand its structure and function. In the storage area of the comb, only honey is stored and no brood is reared. We predicted that honey bees may construct different hexagonal cells for brood rearing and honey storage. We used quantitative analyses to evaluate the structure and function of the natural comb cell in the Chinese bee, Apis cerana cerana and the Italian bee, A. mellifera ligustica . We made cell molds using a crystal glue solution and measured the structure and inclination of cells. We found that the comb cells of A. c. cerana had both upward-sloping and downward-sloping cells; while the A. m. ligustica cells all tilted upwards. Interestingly, the cells did not conform to the regular hexagonal prism structure and showed irregular diameter sizes. In both species, comb cells also were differentiated into worker, drone and honey cells, differing in their diameter and depth. This study revealed unique differences in the structure and function of comb cells and showed that honey bees design their cells with precise engineering to increase storage capacity, and to create adequate growing room for their brood.